Stability challenges of carbon-supported Pt-nanoalloys as fuel cell oxygen reduction reaction electrocatalysts. Issue 100 (6th December 2022) - Đukić, Tina; Pavko, Luka; Jovanovič, Primož; Maselj, Nik; Gatalo, Matija; Hodnik, Nejc
Abstract : The chronological development of Pt-alloys as electrocatalysts and electrochemical characterisation methods in our laboratory. Abstract : Carbon-supported Pt-based nanoalloys (CSPtNs) as the oxygen reduction reaction (ORR) electrocatalysts are considered state-of-the-art electrocatalysts for use in proton exchange membrane fuel cells (PEMFCs). Although their ORR activity performance is already adequate to allow lowering of the Pt loading and thus commercialisation of the fuel cell technology, their stability remains an open challenge. In this Feature Article, the recent achievements and acquired knowledge on the degradation behaviour of these electrocatalysts are overviewed and discussed.